Comparative Analysis of Sell-In-May-And-Go-Away and Monthly Effect Before and During COVID-19 Pandemic at LQ45 IDX - Doan Sitohang; H.M. Roy Sembel; Melinda Malau (Keynesia : International Journal of Economy and Business, 2023)
In 2022, the number of investors in the Indonesian stock market experienced a four-fold growth compared to 2019. This surge occurred during the epidemic period. This financial research aims to analyze the impact of the COVID-19 pandemic on the monthly average return and risk pattern of LQ45, as well as the presence of the Sell-in-May-and-Go-Away (SIMAGA) effect and the optimal investment strategy for LQ45. The study uses a descriptive-comparative methodology and employs mathematical and statistical frameworks. The sample consists of LQ45 companies from 1997 to 2022. Data analysis techniques include the Normality Test, Wilcoxon Rank Test, F Test, and investment strategy simulation. The results indicate that COVID-19 did not have a negative effect on the monthly returns and risk patterns of LQ45, except in 2002. Additionally, the SIMAGA phenomenon is not present in LQ45, but the Sell in August-Buy in November (SIABIN) strategy has been identified as the most effective. These findings provide valuable insights for investors in allocating their investments and determining the best strategy for buying stocks. It is important to consider monthly return variance as a key metric for measuring investment risk and its impact on overall returns.